In vitro replication of adeno-associated virus DNA: enhancement by extracts from adenovirus-infected HeLa cells. - Ward, P (1996)
Previously we have described an in vitro assay for the replication of adeno-associated virus type 2 (AAV2) DNA. Addition of the AAV2 nonstructural protein Rep68 to an extract from uninfected cells supports the replication of linear duplex AAV DNA. In this report, we examine replication of linear duplex AAV DNA in extracts from either uninfected or adenovirus (Ad)-infected HeLa cells. The incorporation of radiolabeled nucleotides into full-length linear AAV DNA is 50-fold greater in extracts from Ad-infected cells than in extracts from uninfected cells. In addition, the majority of the labeled full-length AAV DNA molecules synthesized in the Ad-infected extract have two newly replicated strands, whereas the majority of labeled full-length AAV DNA molecules synthesized in the uninfected extract have only one newly replicated strand. The numbers of replication initiations on original templates in the two assays are approximately the same; however, replication in the case of the Ad-infected cell extract is much more likely to result in the synthesis of a full-length AAV DNA molecule. Most of the newly replicated molecules in the assay using uninfected cell extracts are in the form of stem-loop structures. We hypothesize that Ad infection provides a helper function related to elongation during replication by a single-strand displacement mechanism. In the assay using the uninfected HeLa cell extract, replication frequently stalls before reaching the end of the genome, causing the newly synthesized strand to be displaced from the template, with a consequent folding on itself and replication back through the inverted terminal repeat, using itself as a template. In support of this conjecture, replication in the uninfected cell extract of shorter substrate molecules is more efficient, as measured by incorporation of radiolabeled nucleotides into full-length substrate DNA. In addition, when shorter substrate molecules are used as the template in the uninfected HeLa cell assay, a greater proportion of the labeled full-length substrate molecules contain two newly replicated strands. Shorter substrate molecules have no replicative advantage over full-length substrate molecules in the assay using an extract from Ad-infected cells.